The probabilistic approach to the analysis of the limiting behavior of an integro-diffebential equation depending on a small parameter, and its application to stochastic processes. (1994) - Borisenko, O. V.; Borisenko, A. D.; Malyshev, I. G.
Abstract : Using connection between stochastic differential equation with Poisson measure term and its Kolmogorov's equation, we investigate the limiting behavior of the Cauchy problem solution of the integro differential equation with coefficients depending on a small parameter. We also study the dependence of the limiting equation on the order of the parameter.